Metal and Radioactive Elements Uptake of Wild Agaricus and Agrocybe Species Growing in Samanlı Mountains (Türkiye) - Doğan, Hasan Hüseyin; Şanda, Murad Aydın Şanda (My University, 2022)
Twenty-two element contents were analyzed by ICP-AES equipment in five wild Agaricus and Agrocybe taxa [Agaricus bresadolanus Bohus, A. sylvicola (Vittad.) Peck, A. xanthodermus Genev., Agrocybe paludosa (J.E. Lange) Kühner & Romagn. ex Bon and Agrocybe praecox (Pers.) Fayod] from Samanlı Mountains of Türkiye. The element uptake was observed at the different levels in each Agaricus and Agrocybe species. The highest Pb and P concentrations were determined as 16.74 mg/kg and 1.501 mg/kg in A. sylvicola and A. bresadolanus respectively. Ag, Hg, and P concentrations were determined as 30685 µg/kg, 59781 µg/kg, and 501 mg/kg in A. bresadolanus respectively. A. sylvicola has the highest Ni, Cu, and Mn concentrations as 37.1, 43.63 and 1476 mg/kg respectively, whereas A. praecox has the highest Mo, Ni and P at 0.54 mg/kg, 10.20 mg/kg, and 27.9% respectively. A. paludosa has the highest Zn, Cd, and Ba concentrations of 336.8, 2.26, and 571.5 mg/kg. The highest K concentration was found in A. xanthodermus with 5.31 mg/kg. According to WHO and FAO criteria, there is no important risk for the element uptake for human health if these species would be consumed. Additionally, some radioactive metals were found in mushroom species such as Sr, V, Th, Sc, Ga, and U. People should be careful against radioactive pollution if they consume mushrooms naturally.